Effect of nutrient and moisture management practices on growth and yield of pigeonpea in conservation agriculture based pigeonpea (Cajanus cajan)-wheat (Triticum aestivum) cropping system under limited irrigation - Adarsh Kumar; K.S. Rana; Anil K. Choudhary; R.S. Bana; Amaresh Pradhan (Annals of Agricultural Research, 2022)
A field experiment was conducted at the Experimental Farm of ICAR-Indian Agricultural Research Institute, New Delhi during 2014-15 and 2015-16 to study the effect of nutrient and moisture management practices on growth and yield of pigeonpea in conservation agriculture based pigeonpea-wheat cropping system under limited irrigation. Treatments comprised of four moisture conservation treatments in main-plots viz. no residue + no hydrogel (R0HG0 ), wheat residue in pigeonpea @ 4 t ha–1 + hydrogel @ 2.5 kg ha–1 [WRRP @ 4 t/ha + HGP @ 2.5 kg/ha], pigeonpea residue in wheat @ 4 t ha–1 + hydrogel @ 2.5 kg ha–1 [PRRW @ 4 t/ha + HGW @ 2.5 kg/ha] and pigeonpea and wheat residue in succeeding crop + hydrogel @ 2.5 kg ha–1 [WRRP @ 4 t/ha + PRRW @ 4 t/ha + HGPW @ 2.5 kg/ha]; and four nutrient management practices (100% RDF, 100% RDF + 5 kg Zn/ha, 100% RDF + Zinc-solubilizer (Bacillus endophyticus), and 100% RDF + 5 kg Zn + Zn - solubilizer (Bacillus endophyticus) in sub-plots laid-out in a split-plot design with three replications. It was revealed that moisture conservation and zinc fortification treatments exerted significant effect on enhancing plant growth parameters (plant height, leaf area index and dry matter accumulation), growth indices (CGR and RGR) and grain yield of pigeonpea at all the growth stages during both the year of experimentation. Overall, WRRP @ 4 t/ha+ PRRW @ 4 t/ha+ HGPW @ 2.5 kg/ha significantly increased the growth parameters and yield of pigeonpea over other moisture management practices. Likewise, 100% RDF + 5 kg Zn/ha + Zn-solubilizer exhibited higher growth and grain yield of pigeonpea in a pigeonpea-wheat cropping system under limited irrigation conditions in semi-arid climate of north India.